Meningeal infiltration by non-myelomatous IgD-secreting plasma cell dyscrasias. Issue 766 (August 1989) - Yebra, M.; Manzano, L.; de la Torre, A.; Hornedo, J.; Albarran, F.; Menéndez, J. L.
Abstract : Two cases of meningeal invasion by non-myelomatous plasma cell dyscrasias–a plasma cell leukaemia and an extramedullary plasmacytoma–are described. Both were secretors of IgD paraprotein and both were diagnosed in life, characteristics which we have not found in any other published case of plasma cell leptomeningitis. Analysis of our patients and of another 25 cases suggests as predisposing factors of meningeal invasion the male sex, presentation in the form of plasma cell leukaemia, presence of the IgD paraprotein and tumoral involvement of pleura, lung, pericardium and testicles. Aggressive treatment of this neurological complication controlled the meningeal disorder in some cases. However, the majority died of disseminated disease in spite of systemic chemotherapy. Until an effective treatment can be found, able to maintain remission or cure the systemic disease, prophylaxis of the central nervous system in plasma cell dyscrasias does not appear to be advisable.